REPRESENTATION OF THE TEACHER'S PERSONALITY AND INNER CONFLICT IN THREE INDONESIAN MODERN NOVELS BASED ON A REVIEW OF LITERARY PSYCHOLOGY AND ITS USE AS READING MATERIAL FOR LITERARY CRITICISM COURSES - Zukhruf Ambarsari; Malan Lubis; Mara Untung Ritonga (Journal of Social Research, 2022)
Background: In CPL and CPMK 14 students are required to be able to appreciate and criticize literary works, for example poetry, prose, and drama with several approaches, one of which is by using a literary psychology approach. But in reality there are some students who do not understand this approach very well. This is evidenced by the needs analysis questionnaire that has been distributed to several students, the author sees that students have not been able to criticize literary works based on a review of literary psychology. Objective: Examine the personality of the teacher expressed in three modern Indonesian novels in terms of psychology sastra. Methods: The method used in this study is a qualitative approach. This method aims to break down the analyzed cases according to the needs of the study. Results: The results of this study show that the teacher's personality expressed in three modern Indonesian novels based on literary psychology, namely 1) The character of the teacher in Guru Aini's novel has a highly committed personality, morale, sincerity in work, and has high ambitions, a steadfast spreader in the establishment. 2) The character of the teacher in the novel Kembara Rindu has a trusting, loving, unyielding, loyal, diligent, honest, hard work, self-control, courageous and generous personality. 3) The character of the teacher in Special Child has a patient, responsible, humble, honest, sacrificial and caring personality. The inner conflict of the teacher in three modern Indonesian novels based on a review of literary psychology, namely 1) Guru Aini's novel has an inner conflict of approaching and moving away based on Kurt Lewin's theory. 2) The novel Kembara Rindu has an approaching-approaching inner conflict based on Kurt Lewin's theory. 3) The Special Child novel has an inner conflict that almost moves and moves away based on Kurt Lewin's theory. Consultion: The personality of the teacher expressed in three modern Indonesian novels based on literary psychology, namely 1) The character of the Teacher in the novel Guru Aini has a highly committed personality, morale, sincerity in work, and has high ambitions, steadfast in the establishment. 2) Teacher's Character in the novel Kembara Rindu has a personality of trust, compassion, unyielding, loyal, diligent, honest, hardworking, self-control, courageous and generous.